Extended Use of Distal Embolic Protection Devices in Treatment of Distal Embolism During Lower Extremity Arterial Endovascular Interventions. Issue 3 (May 2022) - Ibrahim, Mudathir; Swearingen, Bruce; Pu, Sirui; Rhee, Robert; Pu, Qinghua
There is no consensus on the best treatment modality for acute distal embolization complications during endovascular interventions for peripheral arterial diseases. We report on 3 patients who underwent mechanical embolectomy using a distal embolic protection device (EPD). All patients showed angiographic evidence of distal embolism, which occurred during lower extremity limb salvage endovascular procedures. After embolectomy, all had complete recanalization of the involved vessel on completion angiogram, and none had any device-related complications or adverse outcomes from the embolization. This initial experience suggests that EPD can be used for both the prevention and treatment of intraoperative distal embolization during endovascular intervention of lower extremity arterial disease.